Peer Supervision as Collaborative Professional Learning for Islamic Religious Education Teachers - Ika Ayu Rohmiyanti; Rahmat Hariyadi (Kognisi: Jurnal Ilmu Keguruan, 2026)
Teacher professional development is most likely to influence practice when it is embedded in teachers’ daily work, collaborative, reflective, and supported by actionable feedback. Peer supervision is one school-based mechanism that can combine these characteristics, yet its enactment in Islamic Religious Education (Pendidikan Agama Islam/PAI) remains underexplored. This study examines how peer supervision was implemented to support PAI teachers’ professional learning at SMPIT Nurul Islam Tengaran, Semarang Regency, Indonesia; the conditions perceived to shape its effectiveness; and its reported contributions to teaching practice. A qualitative case-study design was employed. The source study used purposive sampling, classroom observation, interviews, and document analysis, with evidence reported from the principal, vice principal for curriculum, a PAI teacher serving as peer supervisor, and a supervised PAI teacher. Data were reduced, organized around the research questions, displayed thematically, and interpreted through source and technique triangulation. Findings show that peer supervision had been institutionalized as a once-per-semester cycle involving supervisor-team formation, pre-observation conferencing, lesson preparation, classroom observation, and post-observation feedback. Its developmental value was associated with collegial relationships, negotiated scheduling, leadership encouragement, visible school-wide participation, and follow-up training. Reported outcomes included greater awareness of instructional strengths and weaknesses, more disciplined preparation of teaching modules, increased reflection, and experimentation with active-learning strategies. However, perceptions of impact were not uniform: the supervised teacher viewed changes in teaching quality more cautiously than the supervising teacher, suggesting that the strongest evidence concerns reflective learning and instructional discipline rather than proven causal improvement. The study positions peer supervision as a promising form of collaborative professional learning when it is framed as developmental rather than punitive and linked to sustained follow-up.